Applications of mathematics and physics for the construction of a stress bridge in high school - O’Donnell Krause, Marcelo; Pereira Oliveira, Davi; Luis Arantes Dahlke, João; Filipe Anjos de Carvalho, Ramon; Oliveira Krause, Sarah; Coutinho Costa, Yuri; Ramos Dias dos Santos, Mateus; Moreira da Vitória, Brisa; Santana Ferreira, Glauco; Borges da Silva, Lucas (Seven Editora, 2023)
Through the knowledge acquired by students in mathematics and physics classes with regard to the contents of plane geometry, spatial geometry, force and moment, a proposal was given to build a truss bridge with barbecue sticks in which the system should support a load many times greater than its own weight. Students, even in high school, should research the balance, efforts and construction conditions for a truss system based on literature from the basic disciplines of architecture and engineering courses. The students who developed the project and presented it at a math fair at a local university are part of an applied physics research group. This group is made up of three-year high school students.DOI:https://doi.org/10.56238/alookdevelopv1-010